"The influence of female body mass index, menstrual cycle phase and age on propofol injection pain". Issue 1 (1st January 2021) - Mostafa, Raham Hasan; Kamal, Mohamed Mohamed; Mohamed, Marwa Mamdouh; Ismaiel, Mohamed Abdulmohsen
ABSTRACT: Background : Eliminating propofol injection pain (PIP) should be multimodal, including pharmacological and non-pharmacological interventions. Understanding risk factors – body mass index, menstrual cycle phase and age for example – leading to increased pain sensitivity will identify patients at most risk for PIP, permitting effective treatment strategies to be initiated at an early stage. Objective : Our goal is to determine occurrence and severity of propofol injection pain among female patients, whether they are obese or non-obese, during different menstrual cycle phases. Methods: Design : A prospective observational study. Setting : Single university teaching hospital's operating rooms. Patients : 84 female undergoing surgeries under general anesthesia, classified as American Society of Anesthesiologists (ASA) physical status I–II, between 18 and 65 years of age were enrolled. Interventions : We evaluated propofol injection pain using visual analogue scale (VAS) during induction of general anesthesia. Main outcome measure : The relation between propofol induced peripheral venous pain and female body mass index, menstrual cycle phase and age. Results : 71.4% of patients experienced PIP. Of those patients who experienced PIP; 40.5% (34/84 patients) had moderate to severe pain. Age <35 years was the only independent predictor of moderate/severe PIP (sensitivity 62%, specificity 78%). After adjustment for age category, there was no statistically significant association between occurrence of moderate/severe PIP and obesity or menstruation. Conclusion : Propofol injection pain prophylactic measures should be considered in young females <35 years as they may be more prone to moderate/severe PIP. Trial Registration : NCT04078087